The distribution of Cryphia ochsi Boursin, 1940 and Cryphia algae (Fabricius, 1775) (Lepidoptera: Noctuidae) in Slovenia and Croatia - Gomboc, Stanislav (Acta entomologica slovenica (Ljubljana), 2015)
The distribution of the C. algae/ochsi species complex in Slovenia and Croatia was never a target of any systematic survey. Until now, C. ochsi was known only from the Krk island, Croatia, while no records from Slovenia or other parts of Croatia existed. We carried out a study of these two species in Slovenia and Croatia, based exclusively on the examination of the male and female genitalia to gain an insight into the distribution, phenology and altitudinal range of these two species. The results show that C. ochsi is present mostly in the coastal, generally Mediterranean and Sub-Mediterranean areas of Slovenia and Croatia. On the other hand, C. algae is a widely distributed species, present in most parts of both countries, but is less frequent in the Mediterranean region. C. ochsi is new to Slovenian Lepidoptera fauna. Both species prefer the lower altitudes, i.e. C. ochsi occurs mostly below 200 m a. The flight periods of both species range from June to end of September, in a single, long generation. The peak in their activity is in July and August, with some outstanding findings in April and October.
Keywords: Croatia; Cryphia ochsi; genital structure; Hrvaška; Lepidoptera; metulji; new records; Noctuidae; nove najdbe; Slovenia; Slovenija; sovke; strukture genitalij